COVID-19 Shocks, Performance, and Financing Decisions : Panel Evidence from Indian Firms - Vodwal, Sandeep; Vodwal, Lata (Indian Journal of Finance, 2024)
Purpose : The lockdown and social distancing measures to alleviate the pressure on the healthcare sector to flatten the 2019-nCoV (COVID-19) curve had asymmetrically distressed the performance and short-term financing of Indian firms. This study looked at the performance and short-term debt ratio of the Indian manufacturing and services industries independently, attempting to diagnose the varied effects of COVID-19 regulations. The study also looked into the variations caused by exogenous shocks in the factors determining the short-term debt ratio. Methodology : The study used linear panel data methods and the quarterly panel data of 4,536 enterprises from 2008–2009 to 2021–2022 to achieve its goals. The binary variables techniques were used to study the crisis period. Findings : The results corroborate the notion that the crisis negatively and unevenly impacted Indian industries. For example, the performance of manufacturing companies fell to 69%, while the services sector saw a decline of up to 91%. Similar to how the short-term debt ratio decreased dramatically during the pandemic, the manufacturing sector saw a slight decline, or 0.0204, and the services sector saw a reduction, or 0.0244. The study also noted significant deviations in the determinants of short-term debt ratio; for instance, profit, size, and liquidity were the prime determinants of short-term debt ratio in manufacturing firms. At the same time, liquidity was the sole determinant of the short-term debt ratio for a service sector firm. Theoretical, Managerial, and Practical Implications : The results indicated that the Indian firms were operating sub-optimally because of the demand and market and supply shocks during the COVID-19 period. However, the accessibility and easiness of the financing could help firms to work efficiently. Originality : The biggest upheaval the companies have experienced is the COVID-19 problem. For the businesses, which are the vital sector of the economy, to continue operating throughout the recession, government assistance was necessary. The governments, however, had difficulty determining which areas ought to be prioritized for assistance in order to distribute the scarce resources at their disposal. Thus, it was intended for this study to report on the crucial areas of the companies for successful government interventions.